The Role of MULTIMOD in the IMF's Policy Analysis - Isard, Peter (Washington, D.C. : International Monetary Fund, 2000)
This paper describes the basic structure, underlying philosophy, and key behavioral properties of MULTIMOD. It also focuses on several recent applications of macromodels in the IMF's policy analysis, emphasizing that most questions put forward for analysis with models like MULTIMOD are initially posed in ways that cannot be addressed by simply pushing a computer key. Meaningful macromodel-based policy analysis requires a sensibly structured and parameterized macromodel, but it also generally requires considerable probing of the nature of the policy issues in order to reformulate policy questions in terms of well-defined exogenous shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet